Practical Challenges for Digital Watermarking Applications - Sharma Ravi K; Decker Steve (EURASIP Journal on Advances in Signal Processing, 2002)
The field of digital watermarking has recently seen numerous articles covering novel techniques, theoretical studies, attacks, and analysis. In this paper, we focus on an emerging application to highlight practical challenges for digital watermarking applications. Challenges include design considerations, requirements analysis, choice of watermarking techniques, speed, robustness, and the tradeoffs involved. We describe common attributes of watermarking systems and discuss the challenges in developing real world applications. Our application uses digital watermarking to connect ordinary toys to the digital world. The application captures important aspects of watermarking systems and illustrates some of the design issues faced.